Agronomic effectiveness of unacidulated and partially acidulated Minjingu rockphosphates on Stylosanthes guianensis - Haque, I.; Lupwayi, N.Z.; Ssali, H. (1999)
The majority of soils in Africa are P-deficient, but the high cost of conventional, water-soluble P fertilisers limits their use by resource-poor farmers. Rockphosphates are a low-cost alternative. The relative agronomic effectiveness of unacidulated (RP), 25 percent partially acidulated (PARP25), 50 percent partially acidulated (PARP50) Minjingu rockphosphate and triple superphosphate (TSP) was evalauted at rates of 0-80 kg/ha P on stylo (Stylosanthes guianensis) on an Ultisol in the Ethiopian highlands. The fertilisers were applied once and their effects were followed for 4 consecutive harvests. Stylo dry matter (DM) yields were below 3 t/ha at each cut without applied P and reached as high as 4.8 t/ha when P was applied. Over all 4 cuts, RP was 100 percent, PARP25 was 89 percent and PARP50 was 103 percent as effective as TSP in increasing stylo herbage yields. The corresponding relative responses in P uptake were 103, 79 and 92 percent for RP, PARP25 and PARP50, respectively. The substitution rates for herbage yields were 100 percent for RP, 79 percent for PARPP25 and 106 percent for PARP50 while those for P uptake were 106 percent for RP, 62 percent for PARP25 and 85 percent for PARP50. Significant (P<0.05) effects of P on stylo DM and P uptake were observed at all harvests. It is concluded that raw Minjingu rockphosphate is highly effective on stylo in these soils. This rockphosphate could be used to increase forage production for increased and sustainable crop-livestock productivity on the P-deficient Ultisols.